A review on sensors and systems in structural health monitoring: Current issues and challenges - Hannan M.A.; Hassan K.; Jern K.P. (Techno-Press, 2023)
Damage detection; Data acquisition; Electromagnetic pulse; Energy efficiency; Energy utilization; Monitoring; Real time systems; Sensors; Wireless sensor networks; Civionic; Detailed classification; Future applications; Issues and challenges; Operation frequency; Sensor technologies; Structural health monitoring (SHM); Structure monitoring; Structural health monitoring